2021
DOI: 10.5194/tc-15-4281-2021
|View full text |Cite
|
Sign up to set email alerts
|

Southern Ocean polynyas in CMIP6 models

Abstract: Abstract. Polynyas facilitate air–sea fluxes, impacting climate-relevant properties such as sea ice formation and deep water production. Despite their importance, polynyas have been poorly represented in past generations of climate models. Here we present a method to track the presence, frequency and spatial distribution of polynyas in the Southern Ocean in 27 models participating in the Climate Model Intercomparison Project Phase 6 (CMIP6) and two satellite-based sea ice products. Only half of the 27 models f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…We also considered the possibility of a polynya with thin ice coverage. Setting the sea ice thickness threshold to be 12 cm (consistent with Nakata et al, 2021, andMohrmann et al, 2021), we still found no link between polynya and the AABW outcropping. We suspect that internal dynamics in ECCO drive AABW to outcrop under sea ice, where it loses heat.…”
Section: Interannual Variabilitysupporting
confidence: 88%
“…We also considered the possibility of a polynya with thin ice coverage. Setting the sea ice thickness threshold to be 12 cm (consistent with Nakata et al, 2021, andMohrmann et al, 2021), we still found no link between polynya and the AABW outcropping. We suspect that internal dynamics in ECCO drive AABW to outcrop under sea ice, where it loses heat.…”
Section: Interannual Variabilitysupporting
confidence: 88%
“…In addition, we found significant sensitivities of the sea ice volume calculation to the 1000 hPa air temperature, the sea ice concentration threshold for polynya definition, and the mixed layer depth computation. These could explain why polynyas are so poorly represented in climate models (Mohrmann et al, 2021): the atmosphere, sea ice, and ocean diagnostics need to be accurate simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…We use the daily ARTIST Sea Ice (ASI) Version 5 sea ice concentration (SIC) (Spreen et al, 2008;Melsheimer & Spreen, 2019) with a resolution of 6.25 km×6.25 km on a polar stereographic grid from the Advanced Microwave Scanning Radiometer 2 (AMSR2). We determine the extent of the 2016 and 2017 polynyas during the austral winter (May-October) by applying to these a standard 60% sea ice concentration threshold (Campbell et al, 2019), and "flood fill" algorithm to mask out the open ocean and the Antarctic continent, ice shelves, and adjacent coastal polynyas (Mohrmann et al, 2021). Fig.…”
Section: Sea Ice Concentration From Asimentioning
confidence: 99%
“…However, previous modeling studies suggest a strengthening of the lower limb due to greater AABW formation, mostly in connection with enhanced open-ocean polynya activity near the Antarctica margin relative to baseline simulations (Spence, Sebille, et al, 2014;Hogg et al, 2017;Dias et al, 2021). However, numerical models are often limited in their ability to accurately represent AABW formation, due to insufficient horizontal resolution and a lack of representation of critical overflow processes, leading to an underrepresentation of DSW and a bias towards forming AABW via open ocean deep convection (Heuzé et al, 2015;Dufour et al, 2017;Aguiar et al, 2017;Heuzé, 2021;Mohrmann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%